1997
DOI: 10.1104/pp.114.2.597
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Root Nodule Acid Phosphatase

Abstract: Acid phosphatases are ubiquitous enzymes that exhibit activity against a variety of substrates in vitro, although little is known about their intracellular function. In this study we report the isolation, characterization, and partia1 sequence of the major acid phosphatase from soybean (Clycine max 1.) root nodules. l h e phosphatase was purified predominantly as a heterodimer with subunits of 28 and 31 kD; homodimers of both subunits were also observed and exhibited phosphatase activity. In addition to the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 30 publications
1
57
1
Order By: Relevance
“…Furthermore, the increased intracellular and extracellular phosphohydrolase (APase and phytase) activity, would serve as an additional route of Pacquisition from organically-bound sources of P, during conditions of limiting soil P. The importance of increased APase activity for P metabolism has been extensively reported (Gilbert et al 1998, Miller et al 2001. Intracellular APases break down P nucleotides, sugar-P and P-monoesters and recycle P through the supply of P for amino acid biosynthesis and nodule metabolism during P-deprivation (Penheiter et al 1997). Previous studies have also shown that an increase in intracellular nodule APase activity may constitute an adaptive mechanism for N 2 fixing legumes to tolerate P deficiency (Kouas et al 2008, Bargaz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased intracellular and extracellular phosphohydrolase (APase and phytase) activity, would serve as an additional route of Pacquisition from organically-bound sources of P, during conditions of limiting soil P. The importance of increased APase activity for P metabolism has been extensively reported (Gilbert et al 1998, Miller et al 2001. Intracellular APases break down P nucleotides, sugar-P and P-monoesters and recycle P through the supply of P for amino acid biosynthesis and nodule metabolism during P-deprivation (Penheiter et al 1997). Previous studies have also shown that an increase in intracellular nodule APase activity may constitute an adaptive mechanism for N 2 fixing legumes to tolerate P deficiency (Kouas et al 2008, Bargaz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The major stained bands were excised, and the N-terminal amino acid sequence of the proteins were determined at the University of Nebraska-Lincoln Protein Core Facility (Biosystems Procise 494; Perkin-Elmer Applied Biosystems, Foster City, CA). Proteins that were blocked at the N terminus were subjected to enzymatic digestion and peptide separation according to the method of Penheiter et al (23). Ten bands of a protein (≈30 µg) were cut from 12% SDS-PAGE separation gels and digested with 0.3 µg of trypsin (Sigma Chemical) at 37°C for 20 h. The resultant peptides were fractionated on a 2.1 × 250 mm C18 column (Model 218 TP52, VYDAC, Hesperia, CA) (1 column volume = 0.866 ml) with a linear gradient from 2% CH 3 CN in 0.1% trifluoroacetic acid to 60% buffer B (90% CH 3 CN in 0.09% trifluoroacetic acid) over 15 column-volumes at 0.2 ml/min on a high performance liquid chromatography (Microbore; ISCO, Lincoln, NE).…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antibodies were raised against this r-ns-Hb1 in rabbits by the Antibody Core Facility of the University of Nebraska-Lincoln. Serum titers were analyzed by Western blotting techniques (Penheiter et al 1997).…”
Section: Antibodies To Rice R-ns-hb1 and Immunoblotting Of Native Ricmentioning
confidence: 99%